A first record of gregarious moth pest, Herpetogramma platycapna (Meyrick) of fern species, Angiopteris evecta (G. Forst.) Hoffm from Malaysia - Ghazali, S. Z.; Md-Zain, B. M.; Maideen, H.; Maimon, A.; Yaakop, S. (Penerbit Universiti Kebangsaan Malaysia, 2014)
In this study, a first record on interaction of insect with fern species has been presented from Malaysia. Molecular identification of cytochrome oxidase I gene (COI) has revealed the Herpetogramma platycapna (Meyrick) is the gregarious pest of Angiopteris evecta (G. Forst.) Hoffm. The pest species also has been reconfirmed based on morphological characters.